KONSEP PENDIDIKAN ISLAM DALAM PERSPEKTIF NURCHOLISH MADJID - Mutaqin, Ade Zaenul; Aji Priatna Nurmansyah (Program Studi Pendidikan Agama Islam, 2023)
Understanding the basic concepts of Islamic education must of course have a broad perspective in thinking and application. Because currently it is not very well implemented, both systematically, in relevant processes and evaluations. Therefore, reconstructing the basics of Islamic education in Indonesia as a form of development of Islamic education both philosophically and practically is a real choice now. In this research the author tries to describe several aspects including the objectives, materials and educational methods used by Nurcholish Majid, he is an Indonesian Islamic thinker and reformer. The method used is Qualitative Descriptive, namely by explaining the ideas put forward by Nurcholish Madjid, namely a description of data accompanied by analysis and interpretation using historical, sociological, philosophical and theological approaches. Various aspects of life should refer to fundamental things as principles of life, including divinity, humanity and justice. By using these three principles, that is ideal education, because basically education is a way to humanize humans and to continue to remember their creator. Education emphasizes the concept of forming a noble human being (Insan Kamil), namely the realization of aspects of glory that are even and balanced through Islamic education